2018
DOI: 10.1590/0001-3765201820170323
|View full text |Cite
|
Sign up to set email alerts
|

Pterobothrium crassicolle parasitizing Paralichthys orbignyanus (Osteichthyes, Paralichthyidae) in Brazil

Abstract: From September 2014 to November 2015, 30 Paralichthys orbignyanus specimens were obtained from Sepetiba Bay in the municipality of Rio de Janeiro, State of Rio de Janeiro, Brazil. The fishes were necropsied and cestode larvae were recovered from the abdominal cavity, mesentery, and serosas of the stomach, intestine, spleen, liver, kidney and gonads. Nineteen fish were parasitized by a total of 90 trypanorhynch plerocerci. Based on morphological characters, these were identified as Pterobothrium crassicolle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…There has only been one previously unidentified trypanorhynch species reported for Mugil curema Valencienes, 1836, from local markets on Itamacará Island and at Itapissuma, Northeast Brazil (PALM, 1997). Furthermore, these two species have been reported parasitizing Brazilian teleost and elasmobranch marine fishes (FONSECA et al, 2012;FELIZARDO et al, 2018), being now also reported to the Mugilidae family.…”
Section: Introductionmentioning
confidence: 95%
“…There has only been one previously unidentified trypanorhynch species reported for Mugil curema Valencienes, 1836, from local markets on Itamacará Island and at Itapissuma, Northeast Brazil (PALM, 1997). Furthermore, these two species have been reported parasitizing Brazilian teleost and elasmobranch marine fishes (FONSECA et al, 2012;FELIZARDO et al, 2018), being now also reported to the Mugilidae family.…”
Section: Introductionmentioning
confidence: 95%
“…Adultos habitam o trato gastrointestinal de elasmobrânquios, enquanto larvas ocorrem na cavidade celômica, serosa visceral e musculatura dos hospedeiros intermediários, como cefalópodes, crustáceos e peixes teleósteos (Palm, 2004). Na inspeção do pescado, os cestoides, adquirem importância na inspeção sanitária pelo aspecto repugnante que causam ao consumidor quando os peixes teleósteos apresentam estes parasitos, principalmente em infecções maciças (Felizardo et al, 2018) ou pelo potencial risco de causar a zoonose conhecida como difilobotríase ou reações alérgicas em humanos (Leite et al, 2022). O objetivo do presente estudo foi determinar os espécimes de cestoides parasitos de G. genidens (Cuvier, 1829) coletados na costa do Estado do Rio de Janeiro, Brasil, apresentar seus índices parasitários, de prevalência, intensidade, abundância, sítios de infecção e ressaltar a sua importância higiênico-sanitária, relatando a sua ocorrência, devido a seu potencial zoonótico.…”
Section: Introductionunclassified
“…Adultos habitam o trato gastrointestinal de elasmobrânquios, enquanto larvas ocorrem na cavidade celômica, serosa visceral e musculatura dos hospedeiros intermediários, como cefalópodes, crustáceos e peixes teleósteos (Palm, 2004). Na inspeção do pescado, os cestoides, adquirem importância na inspeção sanitária pelo aspecto repugnante que causam ao consumidor quando os peixes teleósteos apresentam estes parasitos, principalmente em infecções maciças (Felizardo et al, 2018) ou pelo potencial risco de causar a zoonose conhecida como difilobotríase ou reações alérgicas em humanos (Leite et al, 2022). O objetivo do presente estudo foi determinar os espécimes de cestoides parasitos de G. genidens (Cuvier, 1829) coletados na costa do Estado do Rio de Janeiro, Brasil, apresentar seus índices parasitários, de prevalência, intensidade, abundância, sítios de infecção e ressaltar a sua importância higiênico-sanitária, relatando a sua ocorrência, devido a seu potencial zoonótico.…”
Section: Introductionunclassified